PRICE 2020 guidelines for reporting case reports in Endodontics: explanation and elaboration. (2nd May 2020) - Nagendrababu, V.; Chong, B. S.; McCabe, P.; Shah, P. K.; Priya, E.; Jayaraman, J.; Pulikkotil, S. J.; Dummer, P. M. H.
Abstract: Case reports play a key role in showcasing new, unusual or rare disease(s), and the impact of newer therapeutic approaches or interventions. The Preferred Reporting Items for Case reports in Endodontics (PRICE) 2020 guidelines are being introduced exclusively for Endodontics by adapting and integrating the CAse REport (CARE) guidelines and Clinical and Laboratory Images in Publications principles. The PRICE 2020 guidelines have been developed to help authors improve the completeness, accuracy and transparency of case reports in Endodontics and thus enhance the standard of manuscripts submitted for publication. The aim of this document is to provide a comprehensive explanation for each item in the PRICE 2020 checklist along with examples from the literature that demonstrate compliance with these guidelines. This information will highlight the importance of each item and provide practical examples to help authors understand the necessity of providing comprehensive information when preparing case reports. A link to this PRICE 2020 explanation and elaboration document is available on the Preferred Reporting Items for study Designs in Endodontology website at http://www.pride-endodonticguidelines.org .